Wildfire Smoke Particulate Matter Concentration Measurements Using Radio Links From Cellular Communication Networks. Issue 1 (25th March 2021) - Guyot, Adrien; Pudashine, Jayaram; Uijlenhoet, Remko; Protat, Alain; Pauwels, Valentijn R. N.; Louf, Valentin; Walker, Jeffrey P.
Abstract: The monitoring of wildfire smoke is important to help mitigate impacts on people such as by sending early warnings to affected areas. Received signal levels (RSLs) from radio links have been used as an opportunistic way to accurately measure rainfall and humidity. Radio links provide integrated measurements along their paths and are an exceptional untapped resource to complement air quality stations in areas affected by smoke events, or in developing countries without air quality monitoring capability. This study analyzed radio link signal fluctuations during smoke events associated with the 2019–2020 Australian wildfires. Concurrently, the atmospheric boundary layer was characterized using atmospheric soundings and surface observations, as well as air quality proxies such as particulate matter concentrations less than 2.5 μm (10 μm), or PM2.5 (PM10 ). Observations showed that dry air containing large amounts of smoke within a surface layer above the ground acted as a lid, reducing dispersion, trapping and maintaining high ground‐level concentrations of smoke. These conditions also created anomalous propagation conditions for radio links and operational weather radars. Power‐law relations between signal fluctuations and PM10 and PM2.5 were derived based on the link data collected and the closest air quality station observations. While there was variability in retrieval performance across smoke events, the best performance determination coefficients exceeded 0.5, with an RMSE on the order of less than 50 μg m −3 for concentrations of more than 400 μg m −3 . Mid‐range link lengths (5–20 km) provided the best results. Plain Language Summary: Unprecedented mega wildfires in southern and eastern Australia generated considerable amounts of smoke and subsequent hazardous health conditions in Australian capital cities. We analyzed the atmospheric conditions during these smoke haze events within Greater Melbourne. Dry air containing large amounts of smoke sitting above the ground acted as a lid, reducing dispersion, trapping and maintaining high ground‐level concentrations of smoke. Shallow planetary boundary layer at night also contributed to elevated concentrations. These conditions also created anomalous propagation conditions for radio links from cellular communication networks. Unique signal patterns were identified and shown to be related to these specific atmospheric conditions and smoke concentrations by analyzing the received signal levels of these links. It is proposed that these routinely recorded data by telecommunication companies be used to predict smoke concentrations at ground level during haze events. Key Points: The 2019–2020 mega wildfires in Australia created hazardous health conditions due to smoke entrainment within the atmospheric boundary layer Low‐level surface‐based ducting conditions were identified for each of these smoke haze events in Greater Melbourne Radio links signal levels exhibited distinct patterns that can be used to retrieve surface smoke particulate matter concentrations